Adaptive kinship: Jane Rule's domestic geographies of care. Issue 3 (21st May 2021) - Blake, Elizabeth
Abstract: Focusing on two of Jane Rule's novels, The Young in One Another's Arms and Memory Board, this essay treats them as a resource for rethinking the relationship between queerness, kinship, and domesticity. Rather than a fully agential idea of queer kinship—the familiar model of "families we choose"—Rule grounds her model of kinship in shared domestic experience, and in slow and mutual adaptation. Her vision of kinship is profoundly relational, and never homonormative; it is also grounded in the lived experience of disability. For Rule, adaptation is both an interpersonal process and a material one: her novels take place in houses that are adapted to accommodate physical and intellectual disabilities, non-monogamous romantic relationships, communal child-rearing, transient populations, and other unconventional communities of care. Adaptive kinship is a way of opposing state rule, the ideology of genetic lineage, and the hegemony of the couple form. Rule's groups of people, which usually include characters queered by race, disability, citizenship, and other forms of difference in addition to sexuality, become families not because they share a legal or genetic tie or because they have chosen each other, but because they have shared and shaped a domestic space.